Proprietary costs of intellectual capital reporting: Malaysian evidence - Kamardin, Hasnah; Abu Bakar, Robiah; Ishak, Rokiah (Emerald Group Publishing Limited, 2015)
Purpose– The purpose of this paper is to examine the relationship between intellectual capital (IC) performance (value-added intellectual coefficient (VAIC)) and company characteristics with IC disclosure (ICD) in Malaysian listed companies. Design/methodology/approach– Sample of the study is 68 biggest Malaysian companies listed in Malaysian Stock Exchange based on market capitalization in year 2006.The paper follows the classification of ICD by Huang et al. (2007), with three broad IC categories in 45 items. Content analysis was used to collect the IC information from the annual reports.Regression analysis was conducted for VAIC and its components. Log linear analysis was also conducted to cater the possible misspecification in the model.Findings– Results of the study show that VAIC is negatively related to ICD. Further classification of VAIC shows that intellectual capital efficiency and human capital efficiency are negatively related to ICD whilst structural capital efficiency is not related to ICD. Company size and leverage are found to be positively related to ICD.Research limitations/implications– Negative association between VAIC and ICD suggests that companies reduce ICD for competitive advantage reason which supports the proprietary cost theory.The findings of the study may provide some evidence to regulators to enhance the reporting practices of IC for the benefits of users of financial reporting in making relevant decisions. The focus should be given on the reporting of human capital items.Originality/value– This is the first paper to use IC framework by Huang et al.(2007). Consistency of findings with other studies using different IC framework can be compared for the choice of IC framework in future studies.